Comparative Evaluation of Osteogenic Potential of Conventional Glass-ionomer Cement with Chitosan-modified Glass-ionomer and Bioactive Glass-modified Glass-ionomer Cement An In vitro Study - Ranjani, Muthukrishnan Sudharshana (Contemp Clin Dent, 2021)
AIM: The aim of this study was to compare the osteogenic potential of conventional glass-ionomer cement (GIC) with chitosan-modified GIC (CH-GIC) and bioactive glass-modified GIC (BAG-GIC) as a function of time in varying proportions. MATERIALS AND METHODS: CH-GIC was prepared by adding 10 v/v% (Group II) and 50 v/v% (Group III) CH to the commercial liquid of GIC. BAG-GIC was prepared by the addition of 10 wt% (Group IV) and 30 wt% (Group V) of BAG to the GIC powder. Conventional GIC was kept as Group I. Nine round-shaped samples measuring 2 mm thick and 5 mm in diameter were prepared for every experimental material. Human osteosarcoma cells were cultured and cell proliferation was assessed at 24, 48, and 72 h using 3-(4,5-dimethylthiazol-2-yl)- 2,5-diphenyltetrazolium bromide (MTT) assay, and cell differentiation was assessed at 7,14, and 21 days using alkaline phosphatase (ALP) assay. All experiments were done in triplicate. The data obtained were analyzed using one-way analysis of variance and Tukey honestly significant difference post hoc multiple comparisons at 0.05 level significance. RESULTS: Cell culture studies showed a significant increase in proliferative activity and ALP activity in Group II, III, IV, and V than Group I at all-time intervals (P < 0.05). There was no statistically significant difference in osteogenic potential between CH-GIC and BAG-GIC groups. CONCLUSION: The osteogenic potential was significantly higher in CH-GIC and BAG-GIC compared to conventional GIC.